2018
DOI: 10.1200/jco.2017.76.4381
|View full text |Cite
|
Sign up to set email alerts
|

Prospective International Randomized Phase II Study of Low-Dose Abiraterone With Food Versus Standard Dose Abiraterone In Castration-Resistant Prostate Cancer

Abstract: Purpose Abiraterone acetate (AA) is a standard of care for metastatic castration-resistant prostate cancer (CRPC). Despite a large food effect, AA was administered under fasting conditions in its pivotal trials. We sought to test the hypothesis that low-dose AA (LOW; 250 mg with a low-fat meal) would have comparable activity to standard AA (STD; 1,000 mg fasting) in patients with CRPC. Patients and Methods Patients (n = 72) with progressive CRPC from seven institutions in the United States and Singapore were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
116
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 151 publications
(126 citation statements)
references
References 30 publications
5
116
0
Order By: Relevance
“…Many of these oral oncolytic agents have a proven food effect and an alternative dosing strategy could be interesting to investigate . However, only two other oncolytic agents with an alternative dosing strategy combined with food has been studied (e.g., abiraterone and ceritinib) . Even more, the bioequivalence study performed on the reduced dose of ceritinib with a meal resulted in an adjustment of the drug's registration label even before the safety data were known .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of these oral oncolytic agents have a proven food effect and an alternative dosing strategy could be interesting to investigate . However, only two other oncolytic agents with an alternative dosing strategy combined with food has been studied (e.g., abiraterone and ceritinib) . Even more, the bioequivalence study performed on the reduced dose of ceritinib with a meal resulted in an adjustment of the drug's registration label even before the safety data were known .…”
Section: Discussionmentioning
confidence: 99%
“…9 However, only two other oncolytic agents with an alternative dosing strategy combined with food has been studied (e.g., abiraterone and ceritinib). 7,10 Even more, the bioequivalence study performed on the reduced dose of ceritinib with a meal resulted in an adjustment of the drug's registration label even before the safety data were known. 11 Our study aimed to complement the bioequivalent results with GI-toxicity data and patient preference, which results in a more complete understanding of the advantages of the altered intake regimen in patients with cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Abiraterone with prednisone can be given at 250 mg/day and administered following a low-fat breakfast, as an alternative to the dose of 1,000 mg/day after an overnight fast (see "Abiraterone Acetate in M1 CRPC," page 493). 165 The cost saving may reduce financial toxicity and improve compliance.…”
Section: Abiraterone Acetate In Castration-naïve Prostate Cancermentioning
confidence: 99%
“…A randomized phase 2 noninferiority study of 75 patients with M1 CRPC compared 1,000 mg/day abiraterone with prednisone after an overnight fast with 250 mg/day after a low-fat breakfast. 165 The primary endpoint was log change in PSA, with secondary endpoints of PSA response ($ 50%) and PFS. The primary endpoint favored the low-dose arm (log change in PSA, 21.59 vs 21.19), as did the PSA response rate (58% vs 50%), with an equal PFS of 9 months in both arms.…”
Section: Abiraterone Acetate In M1 Crpcmentioning
confidence: 99%
“…In fact, recent work suggests that aggressive treatment strategies can hasten the emergence and spread of resistance [30][31][32][33][34][35][36][37][38][39][40][41]. In addition, numerous studies, both experimental and theoretical, provide evidence that less aggressive treatment strategies may be called for under some conditions [42][43][44][45][46][47][48][49][50], while several clinical trials have also demonstrated advantages of lower dose therapies [50][51][52][53][54][55][56][57][58]. The most frequently cited advantages of less aggressive therapies are reduced off-target selection for resistance and fewer adverse effects for the patient.…”
Section: Introductionmentioning
confidence: 99%